Praca z piosenką - refleksje teoretyczno-praktyczne = Work with a song - theoretical and practical reflections - Kuligowska, Emilia (Zielona Góra: Instytut Pedagogiki. Wydział Pedagogiki, Psychologii i Socjologii. Uniwersytet Zielonogórski)
The article presents the competences and vocal abilities of preschool children and their determinants. It contains proposals for working with a 3-4-year-old child on the example of the author?s song. A distinction was made between rhythmic and melodic exercises based on E. E. Gordon's theory and examples of breathing and articulation exercises tailored to the needs and abilities of a preschool child.
Keywords: emisja głosu; dziecko w wieku przedszkolnym; nauka piosenki; ćwiczenia rytmiczne; ćwiczenia melodyczne; Gordon, Edwin Elias - teoria; voice emission; preschool child; song learning; rhythmic exercises; melodic exercises; Gordon, Edwin Elias - theory